Potential anti-arthritic and analgesic properties of essential oil and viridiflorol obtained from Allophylus edulis leaves in mice - de Matos Balsalobre, Natália; dos Santos, Elisangela; Mariano dos Santos, Sidney; Arena, Arielle Cristina [UNESP]; Konkiewitz, Elisabete Castelon; Ziff, Edward Benjamin; Nazari Formagio, Anelise Samara; Leite Kassuya, Candida Aparecida (Elsevier, 2023)
Ethnopharmacological relevance: Viridiflorol was identified and isolated from the essential oil of Allophylus edulis leaves (EOAE). A. edulis was used as tereré, which is a drink made by the infusion of herbs in cold water, to treat pain (toothache and headache). All anti-nociceptive (analgesic) and anti-arthritic properties of EOAE and viridiflorol have not been completely scientifically clarified. Aim of the study: The aim of the present study was to investigate the analgesic (anti-hyperalgesic and anti-nociceptive) and anti-arthritic properties of EOAE and viridiflorol using in vivo models. Materials and methods: The oral administration (p.o.) of EOAE (30, 100 and 300 mg/kg), viridiflorol (30, 100 and 200 mg/kg), morphine (1 mg/kg, subcutaneous route (s.c.)) and the intraplantar (local) administration (i.pl.) of viridiflorol (100 μg/paw) were tested using formalin model in Swiss mice. EOAE (100 mg/kg, p.o.), viridiflorol (200 mg/kg, p.o.), and dexamethasone (1 mg/kg, s.c.) were tested by zymosan-articular inflammation and in open-field models. Viridiflorol (0.3, 20 and 200 μg/paw) was also tested in carrageenan model, and viridiflorol (200 μg/paw) was also tested in tumor necrosis factor-α (TNF-α), and dopamine (DOPA) models. Results: The oral administration of EOAE (100 and 300 mg/kg, p.o.), viridiflorol (200 mg/kg, p.o.), morphine (1 mg/kg, s.c.) (MOR) and local administration of viridiflorol (100 μg/paw) significantly inhibited edema and nociception in formalin model. Oral treatments with EOAE and viridiflorol (200 mg/kg) did not cause motor impairment in the open field test since they did not reduce locomotor activity. EOAE, viridiflorol and dexamethasone significantly reduced mechanical hyperalgesia, edema, total leukocytes, polymorphonuclear cells, nitric oxide and protein exudation in the zymosan-induced articular inflammation model. The local administration of viridiflorol (200 μg/paw, i.pl.) significantly inhibited mechanical hyperalgesia and edema induced by carrageenan, TNF-α and DOPA. Conclusions: This study confirms the potential anti-arthritic, anti-nocicepttive and anti-hyperalgesic properties of EOAE and viridiflorol. These properties could explain, at least in part, the folk use of A. edulis against including pain (toothache and headache). Viridiflorol could be partially responsible for the EOAE anti-hyperalgesic, anti-nociceptive and anti-arthritic properties and its mechanism of action could involve the inhibition of TNF-α and DOPA pathways.
Keywords: Formalin; Mice; Pain; Sapindaceae; Terpenes; Zymosan